Restoration of rice ecosystem services: ‘ecological engineering for pest management’ incentives and practices in the Mekong Delta Region of Vietnam - Horgan, Finbarr G.; Vu, Quynh; Mundaca, Enrique A.; Crisol-Martínez, Eduardo (MDPI, 2022)
Ecological engineering is an agroecological approach to pest management that has been adopted by thousands of rice farmers in the Mekong Delta Region of Vietnam. Farmers adopted the intervention as part of a heuristic approach to developing the technology. This study assesses the knowledge, attitudes and practices related to ecological engineering among participating and non-participating farmers. Interviews with 315 farmers revealed a diversity of practices under the umbrella of ecological engineering, all of which were associated with the establishment of linear vegetation strips as habitat for natural enemies. As a restoring service from society to the rice ecosystem, ecological engineering incorporated significant positive-feedback loops, particularly regarding the production of supplementary foods (provisioning services) and the aesthetic value (cultural services) of planted rice bunds. Participating farmers reported fewer insecticide applications to their main rice crop; they applied insecticides at a later crop growth stage (protecting pest regulating services); and they reported higher rice yields. However, a high dependency on government support, the role of agrochemical extensionists in providing information, a tendency to apply pesticides to vegetation strips and little change in the appreciation of wildlife-related services all threaten the social sustainability of the intervention. We recommend greater attention to optimizing linear strips to not only support natural enemies but to also enhance supplementary farm incomes while reducing material and labor costs.